COLONIAL RURAL BUILDINGS IN ALGERIA: FROM DISUSE TO VALORIZATION, CASE STUDY OF THE GUELMA REGION - Fouzia Fareh,; Djamel Alkama, (International Journal of Innovative Technologies in Social Science, 2024)
After independence, Algeria inherited a rural built heritage marked by the presence of numerous colonial farms. While some of this heritage has been recovered, it remains largely unknown and undervalued compared to its urban counterpart. Yet these buildings, which bear witness to an era and a way of life, are an invaluable resource for the development of rural areas. This study challenges this neglect by exploring the potential of rural heritage as a catalyst for economic and social revitalization. Case studies from the Guelma region illuminate the practical applications and challenges of repurposing these structures. By examining the economic, social, and cultural dimensions of rural heritage, this research aims to contribute to the development of comprehensive strategies for its preservation and valorization. Key considerations include a deeper understanding of rural built heritage, innovative conservation approaches, and the integration of these efforts into broader rural development plans.